2021
DOI: 10.1001/jamanetworkopen.2021.0814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Keratoconus in Persons With Down Syndrome in a National Registry in Norway

Abstract: This cross-sectional study evaluates the association of keratoconus with Down syndrome by estimation of the prevalence of keratoconus in persons with Down syndrome in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…15 Several studies from general populations have found a male predominance for keratoconus, 3 6 40 54-56 although this finding has not been consistent. 2 5 39 57 In this literature review, we identified one publication that found a similar gender distribution among persons with Down syndrome and keratoconus, 22 which is consistent with our recent publication, 34 otherwise, the gender distribution does not seem to have been in focus. There seem to be slightly more male than female persons with Down syndrome.…”
Section: Open Accesssupporting
confidence: 80%
See 4 more Smart Citations
“…15 Several studies from general populations have found a male predominance for keratoconus, 3 6 40 54-56 although this finding has not been consistent. 2 5 39 57 In this literature review, we identified one publication that found a similar gender distribution among persons with Down syndrome and keratoconus, 22 which is consistent with our recent publication, 34 otherwise, the gender distribution does not seem to have been in focus. There seem to be slightly more male than female persons with Down syndrome.…”
Section: Open Accesssupporting
confidence: 80%
“…16 23 26 28 29 33 Thus, a total of 19 articles met the inclusion criteria for the review. In addition, we have included results from our recently published nationwide register study of the keratoconus prevalence in persons with Down syndrome 34 As shown in table 1, the reported rates in these publications ranged from 0% to 71%. Another three studies were considered relevant, although they did not quantify the rate of keratoconus: one study found a high proportion of astigmatism and myopia in persons with Down syndrome 14 ; another found a steeper corneal curvature on topography in persons with Down syndrome compared with controls 35 and a third showed that corneal topographic changes in persons with Down syndrome were more similar to mild keratoconus than in controls.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations